ANISA’S CONFLICT IN THE NOVEL OF WOMEN WITH THE SORBAN BY ABIDAH EL KHALIEQY - Rahmi Bin Musaad; Inriati Lewa; Mardi Adi Armin (International Journal of Social Science, 2022)
This study aims to reveal the inner conflict experienced by the main character Anisa in the novel Perempuan Berkalung Sorban by Abidah El Khalieqy. This is expressed through the form of Anis' character's inner conflict which is depicted in the novel Perempuan Berkalung Turban by Abidah El Khalieqy. This research was conducted by utilizing the theory of literary psychology. This research is qualitative with the direct involvement of researchers in the entire research process starting from problem determination, literature review, data collection and processing, analysis process, and arriving at research conclusions. The results showed that there was a picture of the inner conflict experienced by the main character Anisa, whether carried out by the father, mother or husband as the head of the family and the local community. The forms of verbal violence and physical violence experienced made the psychology of Anisa's character shaken and experienced inner conflict.